2012
DOI: 10.1021/es301234m
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Fullerene Nanoparticles (nC60) in Saturated Sand and Sandy Soil: Controlling Factors and Modeling

Abstract: Understanding subsurface transport of fullerene nanoparticles (nC(60)) is of critical importance for the benign use and risk management of C(60). We examined the effects of several important environmental factors on nC(60) transport in saturated porous media. Decreasing flow velocity from approximately 10 to 1 m/d had little effect on nC(60) transport in Ottawa sand (mainly pure quartz), but significantly inhibited the transport in Lula soil (a sandy, low-organic-matter soil). The difference was attributable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 32 publications
6
40
0
Order By: Relevance
“…1-1a, 1-1b, 1-4a, and 1-4b) also indicated that more CBNPs can attach to the surface of quartz sand at lower flow rates than at higher flow rates. Similar findings have been reported for carbon nanomaterials (fullerene, SWCNT, MWCNT) by several researchers (Jaisi and Elimelech, 2009;Lecoanet and Wiesner, 2004;Li et al, 2008;Liu et al, 2009;Mekonen et al, 2013;Zhang et al, 2012a), demonstrating that mobility of carbon nanomaterials in porous media was enhanced as flow rate increased. Extent of CBNP attachment is expected to decrease with an increment in flow rate (pore water velocity, v), because the interaction time between CBNPS and quartz sand decreases as v increases.…”
Section: Effect Of Metal Oxide Presence and Flow Rate On Cbnp Transportsupporting
confidence: 89%
See 1 more Smart Citation
“…1-1a, 1-1b, 1-4a, and 1-4b) also indicated that more CBNPs can attach to the surface of quartz sand at lower flow rates than at higher flow rates. Similar findings have been reported for carbon nanomaterials (fullerene, SWCNT, MWCNT) by several researchers (Jaisi and Elimelech, 2009;Lecoanet and Wiesner, 2004;Li et al, 2008;Liu et al, 2009;Mekonen et al, 2013;Zhang et al, 2012a), demonstrating that mobility of carbon nanomaterials in porous media was enhanced as flow rate increased. Extent of CBNP attachment is expected to decrease with an increment in flow rate (pore water velocity, v), because the interaction time between CBNPS and quartz sand decreases as v increases.…”
Section: Effect Of Metal Oxide Presence and Flow Rate On Cbnp Transportsupporting
confidence: 89%
“…From the Maxwell model, α theory in CaCl 2 0.1 mM was 7.93 × 10 − 5 , which was 3.5 times larger than that (2.29 × 10 − 5 ) in NaCl 0.1 mM (Table 3), demonstrating that the attachment of CBNPs to quartz sand in CaCl 2 0.1 mM could be greater than that in NaCl 0.1 mM. Similar findings have been reported by Zhang et al (2012a) who performed column experiments to determine the effect of NaCl and CaCl 2 on the transport behavior of fullerene nanoparticles in Ottawa sand and Lula soil. These authors demonstrated the greater impact of Ca 2+ (enhancement of fullerene deposition on porous media) than Na + on the transport of the fullerene.…”
Section: Effect Of Ionic Strength and Ph On Cbnp Transportsupporting
confidence: 84%
“…The influence of cations on the behaviour of CNMs is well illustrated by the extent to which physical straining (filtering out) of nC 60 occurs in saturated porous media. Zhang et al (2012a) found that columns of pure quartz resulted in very limited nanoparticle deposition even at low flow velocities, whereas a heterogeneous sandy soil with low OM content and small, irregular and rough grains of sand, significantly inhibited nC 60 transport. With the addition of CaCl 2 , greater deposition of nC 60 www.soil-journal.net/1/1/2015/ SOIL, 1, 1-21, 2015…”
Section: The Impact Of Soil Organic Mattermentioning
confidence: 93%
“…For both the sand and soil columns, Ca 2+ had a much larger effect on the transport of nC 60 than Na + at the same ionic strengths . This most likely occurred due to efficient neutralisation of surface charges on both nC 60 and sand and soil particles by Ca 2+ relative to Na + , which reduced the electrostatic repulsion (Kuznar and Elimelech, 2004;Zhang et al, 2012a). When considering the fate and behaviour of CNMs in soils, solid peat may have a different impact to that of molecular DOM under environmentally relevant ionic conditions.…”
Section: The Impact Of Soil Organic Mattermentioning
confidence: 99%
“…Straining refers to both wedging (retention of particles at two bounding surfaces) and bridging (when multiple particles collide and are retained in a pore constriction) (Bradford and Torkzaban, 2008;Zhang et al, 2012). Straining occurs when a nanoparticle is physically removed from flow by the size of the channel, which is prevalent in cases with larger nanoparticles or smaller porous media size.…”
Section: Transport Of Sm-nzvi In the Absence Or Presence Of Cu 2+mentioning
confidence: 99%